Evaluation of immunomodulatory and microbicidal potential of Thuja occidentalis - Satish Kumar Verma; Santosh Kumar Singh; Shivsharan Singh; Abhishek Mathur (Environment Conservation Journal, 2010)
The present paper deals with the investigation for in vitro antimicrobial properties and immunomodulatory potential of Thuja occidentalis. Its various solvent extracts showed high potency of antimicrobial activities against bacterial pathogens. The growth of the bacteria Escherichia coli was found to be inhibited by all plant extracts. Staphylococcus aureus was found to be resistant to Hexane extract. While Ethanol extract inhibited the growth of Staphylococcus aureus. Salmonella typhimuruim cultures were inhibited by all extract. Water extracts were more effective against microbial cultures at high concentrations. Rapid rise in total WBC counts in treated organisms proved the plant to have high immunomodulatory property. Plant methanolic extract treated animals showed increased life span than untreated controls. ANOVA analysis of the results showed that the results were significant and reproducible.